Meningkatkan keharmonisan keluarga melalui solution focused family therapy - Rifdha Wahyuni (Procedia : Studi Kasus dan Intervensi Psikologi, 2022)
Communication between family members is an important thing that must always be built, because without positive communication there will be problematic interactions in the family. The family in this case consisted of father (58 years), mother (52 years) and child (26 years). The father is a retiree, the mother is a housewife and the children are private employees. This family complains about family conditions that are less harmonious. This is characterized by minimal interaction at home and poor communication. Based on  the assessment results, it was found that there was unhealthy communication between family members and poor interaction patterns which resulted in low family harmony. The intervention applied to the family is solution-focused family therapy. The aim of the intervention is to improve family harmony by improving patterns of communication and interaction within the family. The results of the intervention show changes in communication and interaction patterns that have an impact on increasing family harmony.